Coping strategies adopted by frontline nurses in dealing with COVID‐19 patients in a developing country during the pandemic: A qualitative study - Moustaq Karim Khan Rony; Muhammad Mostafijur Rahman; Md. Abdullah Al Saki; Mst. Rina Parvin; Hasnat M. Alamgir (Wiley, 2023)
Abstract Aim This study aimed to explore the coping strategies adopted by frontline nurses in dealing with COVID‐19 patients during the pandemic in Bangladesh. Design A qualitative descriptive study. Methods Purposive sampling was used to recruit seventeen frontline nurses from three COVID‐19‐specific hospitals in Dhaka City. In‐depth online interviews and semi‐structured questionnaires were used to collect data through the Google Meet platform. Interview sessions audio-video were recorded, interpreted, analysed, verbatim transcribed and quotes of the participants were verified by member checking. Thematic analysis was used in this research. The study's reporting guidelines were based on the consolidated criteria for reporting qualitative research. Results Seven themes were identified after careful data analysis: (i) A positive attitude in dealing with challenging situation, (ii) Intimate partner's influence, (iii) Self‐emotional regulation, (iv) The tendency to avoid negativity, (v) Motivated by professional obligations, (vi) Religious influence, (vii) Recreational activities. No patient or public contribution This study explored various coping strategies employed by frontline nurses in caring for COVID‐19 patients. No patient or public contribution was investigated.